1456 Back-To-Back Surgeries: A Clinic Case Report Regarding Multiple Complex Spinal Surgeries for Treatment of Multiple Osteochondroma With Histological Conversion to Chondrosarcoma. (12th October 2021) - O'Halloran, A; Gallagher, N; Farrell, T; Darwish, S; Morris, S
Abstract: Background: Multiple Hereditary Osteochondromas [MHO], previously known as multiple hereditary exostoses, is a rare disorder of bone growth, whereby osseous transformation of the cartilage caps within the diaphyses of long bones or flat bones within the skeleton occurs. A significant complication of MHO is the conversion of any present osteochondroma into a malignant chondrosarcoma. Chondrosarcomas are mesenchymal, non-meningothelial tumours and most commonly present with insidious pain, associated neurological deficit by means of impingement of underlying nerves. Case presentation: We present a clinical case of a 29-year-old female medical student with a background history of multiple hereditary osteochondromas. A previously competitive cross-fitter, she developed the conversion of MHO into a malignant chondrosarcoma. Presenting to outpatient clinic in late 2017, this lady had a 2-year history of lower back pain and an associated palpable lump. An MRI of the thoracolumbar spine demonstrated a large mass arising from the posterior elements of T11 to L2. A biopsy at the time was found to be of benign pathology, most likely in keeping with this patient's diagnosis of MHO. The patient returned for review in early 2018, where a repeat MRI showed extension of the previously described lesion into the spinal canal at the level of L1 vertebra. This was concerning that this previously identified osteochondroma lesion could be undergoing malignant transformation. The patient went on to have a series of complex spinal surgeries which we will discuss below.